"Fantasy" and "Prophecy" in E.M. Forster - Ng, Kar-Man Raymond (My University, 1982)
In Aspects of the Novel, Forster discusses the function and importance of "fantasy" and "prophecy", fictional elements that play an essential role in his own works. The object of this study is to provide a definition of these two terms, and to apply them to an evaluation of Forster's two most renowned novels--Howards End and A Passage to India.
Keywords: English; English Language and Literature; English Language and Literature